Therapeutic efficacy of certain treatment protocols for endometritis in crossbred cows - B P, RAVI KUMAR; M, DEVRAJ; T G, HONNAPPA; A, KRISHNASWAMY (The Indian Journal of Animal Reproduction, 2023)
The efficacy of five different protocols of intrautenne treatment for endometritis was investigated in crossbreddairy cows. The protocols followed were EDTA + Tris, EDTA + Tris + antibiotic, lysozyme, lysozyme +antibiotic and antibiotic. The antibiotic used alone or in combination was based on the results of sensitivity test.As indicated by the recovery from endometritis and subsequent conception, the intrauterine administration oflysozyme + antibiotic gave best results among the protocols followed. The intrauterine therapy using EDTA + Tris+ antibiotic also resulted in good recovery from endometritis and subsequent conception. The results of the studyhave indicated the possibility of using lysozyme. Tris and EDTA alone or in combination wilh antibiotic forsuccessful treatment of uterine infections without the possibility of development of resistant bacterial strains.
Keywords: Cows; EDTA; endometritis; tris; lysozyme; antibiotic